Sphingomonas paucimobilis keratitis post cataract surgery: First case report from India - Acharya, Manisha; Farooqui, Javed Hussain; Spencer, Hayden; Arora, Vinay; Mathur, Umang (Nepalese Journal of Ophthalmology, 2019)
Sphingomonas paucimobilis is a rare, aerobic Gram-negative soil bacillus rarely associated with intraocular infections. With only 3 cases of ophthalmic manifestations reported so far, we are presenting the fi rst case of S. Paucimobilis, causing keratitisafter cataract surgery, from India. The organism, which was resistant to initial medical treatment, eventually responded to a patch graft and the patient improved to a final visual acuity of 20/40.